2020
DOI: 10.1111/micc.12650
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic interventions to restore microcirculatory perfusion following experimental hemorrhagic shock and fluid resuscitation: A systematic review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 87 publications
(214 reference statements)
1
10
0
Order By: Relevance
“…As a consequence, ROS formation increases with cellular edema as result (61). Interestingly, a recent review by our group describes a similar efficiency of this specific treatment strategy in restoring microcirculatory perfusion following hemorrhagic shock and fluid resuscitation (5). Combining these results confirms the proposed role of microvascular leakage as underlying mechanism for microcirculatory perfusion disturbances, and recommends targeting oxidative stress and apoptosis pathways as treatment strategy to restore both microvascular leakage and microcirculatory perfusion following hemorrhagic shock and fluid resuscitation.…”
Section: Oxidative Stress and Apoptosissupporting
confidence: 59%
See 1 more Smart Citation
“…As a consequence, ROS formation increases with cellular edema as result (61). Interestingly, a recent review by our group describes a similar efficiency of this specific treatment strategy in restoring microcirculatory perfusion following hemorrhagic shock and fluid resuscitation (5). Combining these results confirms the proposed role of microvascular leakage as underlying mechanism for microcirculatory perfusion disturbances, and recommends targeting oxidative stress and apoptosis pathways as treatment strategy to restore both microvascular leakage and microcirculatory perfusion following hemorrhagic shock and fluid resuscitation.…”
Section: Oxidative Stress and Apoptosissupporting
confidence: 59%
“…As adequate microcirculatory perfusion is essential for tissue oxygenation, there is a need for additional therapeutic strategies to reduce microvascular leakage and thereby improve outcome following hemorrhagic shock. A recent review performed by our group showed that by targeting endothelial barrier function, microcirculatory perfusion could successfully be restored following hemorrhagic shock and fluid resuscitation (5). This emphasizes the relation between microvascular leakage and microcirculatory perfusion and proposes the reduction of microvascular leakage as treatment strategy to restore microcirculatory perfusion and eventually reduce multiple organ failure.…”
Section: Introductionmentioning
confidence: 92%
“…The high lactate AUC in subjects with a low functional capillary density (PVD < 18 mm/mm 2 ) and high heterogeneity (MHI > 0.4) indicates an increased intensity of cellular hypoxia that occurred during the first 6 h of resuscitation. This is an important finding, as traditional resuscitation strategies applied to patients with postoperative shock such as intravenous fluid administration, vasopressors, nitric oxide donors, anticoagulants, or anti-inflammatory agents may provide greater patient benefit if used to target microcirculation-specific derangements (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…© 2021 The Authors. Physiological Reports published by Wiley Periodicals LLC on behalf of The Physiological Society and the American Physiological Society 2 of 2 | EDITORIAL acidemia, hypothermia, and hemodilution that reduces the oxygen-carrying capacity of blood (Leeuwen et al, 2020). The hope is that new treatment modalities might attenuate our reliance on massive volume resuscitation and blood transfusions.…”
Section: Hemorrhagic Shock and Fluid Dynamicsmentioning
confidence: 99%
“…While volume resuscitation is an essential part of treatment for the hemorrhagic patient, it does not necessarily account for the physiologic and molecular changes at play in the microcirculation. Additionally, aggressive volume resuscitation has known deleterious side effects including edema formation, acidemia, hypothermia, and hemodilution that reduces the oxygen‐carrying capacity of blood (Leeuwen et al, 2020). The hope is that new treatment modalities might attenuate our reliance on massive volume resuscitation and blood transfusions.…”
mentioning
confidence: 99%